Obstructed left – sided Amyand’s hernia in a toddler - Sheng, Tan Shong; Mohd Shah, Mohd Shahrulsalam; Omar, Norsuhana (Bangladesh Journal of Medical Science, 2023)
Amyand’s hernia refers to an inguinal hernia which contained the vermiform appendix in the hernia sac. It is more commonly found on the right side in relation to anatomical location of the vermiform appendix and left – sided Amyand’s hernia is very rare. Herein, we report a case of left – sided Amyand’s hernia with bowel obstruction in a 1 year 4 months old boy. The left groin mass was firm and tender, with skin erythema. However, the mass could not be completed incarcerated into the abdominal cavity. His abdomen was distended with sluggish bowel sound. A diagnosis of intestinal obstruction secondary to obstructed left inguino – scrotal hernia was made, and laparotomy was performed. During laparotomy, transverse skin incision was made on the upper abdomen, and the left inguinal canal was opened in accordance with the usual inguinal hernia repair. The hernia sac contained the appendix, caecum and twisted terminal ileal loops. Small bowel resection with primary anastomosis was performed with left herniorrhaphy. Appendix was preserved due to its normal appearance. He remained well during follow up with no hernia recurrence and testicular atrophy Bangladesh Journal of Medical Science Vol. 22 No. 02 April’23 Page : 449-453